Defatted microalgae Haematococcus pluvialis: A sustainable source for gold recovery - Adhikari, Jhapindra; Pang, Gehui; Morisada, Shintaro; Kawakita, Hidetaka; Ohto, Keisuke; Inoue, Katsutoshi; Demura, Mikihide; Maeda, Shuuji; Nakamizo, Kosuke (Journal of environmental chemical engineering, 2024)
The defatted microalgae Haematococcus pluvialis (HP), obtained from various production lots, were subjected to two different treatments: drying without chemical treatment (DH1, DH2, and DH3) and treatment with concentrated sulfuric acid (TH1, TH2, and TH3). These treated materials were employed as efficient and eco-friendly adsorbents to investigate the adsorption behavior of Au(III) in acidic chloride media. The treated adsorbents demonstrated exceptional performance, achieving 100 % adsorption of Au(III) across a broad range of hydrochloric acid (HCl) concentrations from 0.01 to 5.00 M, whereas the dry adsorbents exhibited up to 90 % adsorption only at low HCl concentrations. Both dry and treated adsorbents exhibited superior selectivity for Au(III) in the presence of a mixture of precious metal ions. The adsorption isotherms of Au(III) followed the Langmuir type of adsorption mechanism, and the maximum adsorption capacities for Au(III) were estimated as 1.57, 0.88, and 1.52 mol kg–1 for DH1, DH2, and DH3, and 6.17, 4.80, and 5.37 mol kg–1 for TH1, TH2, and TH3, respectively. The adsorbed Au(III) ions were reduced to the elemental state, as confirmed by X-ray diffraction patterns, scanning electron microscopy/energy-dispersive X-ray analyses, and digital micrographs of the adsorbents after Au(III) adsorption. Successful desorption of the adsorbed Au(III) was achieved using acidic thiourea solution. [Display omitted] •Defatted microalgal adsorbents were prepared with or without treating with concentrated H2SO4.•Adsorbents treated using concentrated H2SO4 exhibited better Au(III) adsorption capacity and selectivity.•Au(III) was reduced to metallic form during the adsorption.•Loaded and reduced Au was successfully desorbed using HCl and thiourea mixed solution.•Component of microalgae would affect the adsorption behavior.